Refining Theories of Change - Lovely Dhillon; Sara Vaca (The Evaluation Center at Western Michigan University, 2018)
Background: Despite the disparities in how they are defined and what elements are included, most Theories of Change remain consistent in one way - their visual format. Typically, Theories of Change are presented as a one-page visual in a flowchart style with lines and boxes of uniform size. In addition, Theories of Change are often created as stand-alone tools that are rarely linked effectively to other organizational tools. Purpose: The authors: (1) propose the essential elements that contribute to robust Theories of Change and clarify the characteristics that distinguish Theories of Change from other organizational tools and formats; (2) suggest additional elements for inclusion in the Theory of Change; (3) present graphic alternatives that allow for an evolution in representing their complexity and depth; and (4) provide ways to link Theories of Change to other organizational tools to increase organizational alignment, efficiency, and, most importantly, impact. Research Design: NA Data Collection and Analysis: NA Setting: NA Intervention: NA Findings: NA Keywords: theories of change, logic models, evaluation, causal strands, mechanisms, assumptions, hypothesis, data visualization, organizational tools, innovation.